Study protocol for measuring stigmatization in persistent tic disorders: development and validation of the Tourette discrimination-stigmatization scale - Martindale, Jaclyn M.; Ringheanu, Victor M.; Pring, Kelly A.; Norona, Sandra; Wiseman, Kimberly; Strowd, Roy E.; Chapman, Leah; Rigdon, Joseph; Rapp, Stephen R.; Storch, Eric A.; Ip, Edward; Mink, Jonathan W. (Frontiers in Psychology, 2024)
Persistent Tic Disorders such as Tourette Syndrome are common neurodevelopmental disorders that are highly stigmatized. Many individuals with Persistent Tic Disorders experience peer rejection, loneliness, and self-stigma. Experiencing stigmatization during childhood can influence the persistence of moderate-to-severe tics later in life. Additionally, these factors have been associated with increased suicidal ideation, suicide attempts, and psychiatric symptom severity. There is a need for interventions to reduce stigma and stigmatization in Persistent Tic Disorders. Before developing cost-effective interventions to mitigate stigma's profound downstream health impacts, a reliable measure of stigmatization must be created. The overarching goal of this research is to develop and validate the Tourette Discrimination-Stigmatization (TD-STIGMA) Scale. Methods: This paper presents the study protocol for developing and validating the TD-STIGMA Scale. The study is designed as a mixed methods study to develop the TD-STIGMA scale and evaluate its psychometric properties. The study uses a phased approach: (1) collection of narrative and thematic content data through in-depth qualitative interviews of stakeholders, (2) development of a novel TD-STIGMA self-report scale using the Delphi Method based on these results, and (3) completion of analyses to determine the scale's psychometric properties (confirmatory factor analysis, convergent, known-group, criterion validity, and test-retest reliability). Discussion: This project will result in a personalized approach to stigma measurement about youth and young adults with Persistent Tic Disorders, which to date does not exist. There are several limitations. Comorbidities or spiritual or cultural beliefs may affect perceptions of stigma and are not directly assessed in this study. We will utilize institutional resources for community outreach to purposefully sample underrepresented minorities who may be at disproportionate risk of adverse outcomes. However, this may not be fully representative of the generalized tic population. The study team will be purposeful in maintaining participant engagement for study retention. Lastly, participants from a tertiary referral center may not fully represent the generalized tic community. However, we hope our broad recruitment strategy and virtual study visits will facilitate a diverse and inclusive sampling of the patient population.